1974
DOI: 10.1530/jrf.0.0390029
|View full text |Cite
|
Sign up to set email alerts
|

Closure of the Uterine Lumen at Implantation in Senescent Golden Hamsters

Abstract: Summary. The uterus of the senescent hamster was examined for the appearance of a luminal closure reaction which normally coincides with implantation in the young animal. Closure in the aged animal was observed only near areas of implanting embryos. Both closure and implantation in the senescent female were found to be delayed approximately 12 hr. Possible correlations between the observations in this study and the decline in fecundity in aged animals is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The same situation was noted in the old rat [66]. In senescing golden hamsters, both closure and implantation were deferred by approximately 12 h and luminal closure was found only around the implanting embryos [67]. Where embryos were not present, the lumen remained open and branched and luminal epithelial cells had tall, regular microvilli which did not contact microvilli from the opposing epithelial border.…”
Section: Humanmentioning
confidence: 58%
“…The same situation was noted in the old rat [66]. In senescing golden hamsters, both closure and implantation were deferred by approximately 12 h and luminal closure was found only around the implanting embryos [67]. Where embryos were not present, the lumen remained open and branched and luminal epithelial cells had tall, regular microvilli which did not contact microvilli from the opposing epithelial border.…”
Section: Humanmentioning
confidence: 58%
“…Where implantation sites were found, an attachment reaction was seen, and it was suggested that an impaired epithelial response to estrogen might be one of the causes of implantation failure in aged mice. In senescing golden hamsters, both closure and implantation were delayed by approximately 12 hours and luminal closure was found only in the vicinity of implanting embryos (Thorpe et al, 1974). Where embryos were not present, the lumen remained open and branched and luminal epithelial cells had tall, regular microvilli which did not contact microvilli from the opposing epithelial border.…”
Section: Age-related Changes In the Endometrium Epitheliummentioning
confidence: 99%
“…This aids closure of the total uterine lumen to achieve close apposition between the blastocyst and apical surface of UECs (Lindsay & Murphy 2005, 2006. It is important to note that luminal closure occurs all along the uterine horn and not just in the implantation chamber (Thorpe et al 1974, Png & Murphy 2000. In previous studies, syntaxin 3 has been shown to interact with sodium channels in epithelial cells, where they regulate intrinsic properties and cell-surface expressions of channels (Saxena et al 1999).…”
Section: Discussionmentioning
confidence: 99%